A novel program to enhance pediatric emergency medicine training in Thailand. Issue 3 (2nd May 2021) - Burns, Beech; Bailey, Jessica; Hartenstein, Melinda; Sullivan, Danielle; Burns, Erin; Lin, Amber; Chan, Daniela; Plainkum, Parit; Techapaitoon, Surangkana; Pandee, Uthen; Ma, O. John
Abstract: Background: In Thailand, there are few pediatric emergency medicine (PEM) fellowship‐trained providers, and emergency departments (EDs) are staffed by pediatricians and emergency physicians. Our pediatric ED collaborated with Thailand's largest private hospital system to develop a training program designed to improve emergency care for children. Objective: The objective was to develop, implement, and assess the efficacy of a curriculum to improve PEM care by emergency providers in a Thai health system. Methods: We conducted a prospective study from January 2018 to July 2019. After an initial needs assessment, we developed a curriculum with 22 modules, divided into basic and advanced courses. Each course began with baseline testing, consisting of written tests and several simulated cases led by physician–nurse teams. Each course was administered longitudinally through electronic modules over 6 months, with in‐person shadowing and skills workshops at the course midpoint, culminating in final summative examinations and repeat simulation testing. Results: On written examination scores for the basic course, physicians ( n  = 5) improved by 37.6% (95% confidence interval [CI] = 29.8% to 45.4%, p < 0.001), while nurses ( n  = 5) improved by 55.7% (95% CI = 45.8% to 65.6%, p < 0.001). For simulation testing among physician–nurse dyads, performance improved by 19.5% (95% CI = 3.9% to 35.1%, p = 0.004) for critical action items and by 3.0 points (95% CI = 2.3 to 3.7, p < 0.001) on a 16‐point teamwork scale. For the advanced course, physicians improved on the written examination by 36.9% (95% CI = 29.2% to 44.7%, p < 0.001) and nurses by 50.6 (95% CI = 47.3% to 54.0%, p < 0.001). For simulation testing, performance improved from 22.2% (95% CI = 8.2% to 35.6%, p < 0.001) for critical actions and 1.3 points (95% CI = 0.2 to 2.2, p = 0.005) on teamwork measures. Conclusions: We designed an interdisciplinary curriculum and successfully trained Thai physicians and nurses to improve PEM knowledge and teamwork.